A inserção do fonoaudiólogo em instituições educacionais de Salvador - Fonteles, Ingrid Barreto Aguiar (2007)
The objective of this study was to research what reasons sustain the educational phonoaudiologics exercise practices in the regular scholastic field, in Salvador s county. To comprehend these reasons were accomplished many directed interviews with important professionals to solve our research issue: phonoaudiologists and school coordinators. The interviews were recorded and transcript in regular orthography. The speech was organized in collection of topics and analyzed as of the analysis technique of content described by Bardin (1979), which propose an analysis by categories. The analytic process of the discursive content allowed the formulation of four categories deductive , resulting from the interview s questions. The categories are: How he gets at School; Developed Work; Relationship with the Phonoaudiologyst and/or Phonoaudiology; and Condition to Insertion. These categories guided the analysis, as the presentation and the data debate. The data analysis allowed us to realize that it s needed to remold the Phonoaudiologyst roll in Salvador´s schools as well to the supervisors and Phonoaudiologysts. The activities accomplished at the schools are mainly centered in the speech modifications and are qualified mainly by the phonoaudiologic consultancy. Phonoaudiology and Education in the capital of Bahia, in a general way, they didn t detect in the low complexity actions in the health area. There isn t demand to prevent niether to a health promotion from the school. It s the Phonoaudiologist responsibility to reintend his roll before the educational reality, in order to seek for insertion in the scholastic area so that can contribute with the school, for a language and communication health